2007
DOI: 10.1159/000100931
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Hyperamylasaemia in Association with Multiple Myeloma

Abstract: Marked hyperamylasaemia associated with an amylase-producing multiple myeloma appears to be a fairly unusual phenomenon. The present report describes a fatal case of multiple myeloma associated with paraneoplastic hyperamylasaemia without evidence of pancreatic or salivary gland involvement. Serum and urine amylase levels paralleled the myeloma response to chemotherapy and disease progression. The importance of paraneoplastic hyperamylasaemia as a useful myeloma marker to monitor disease progression and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Evidence suggests that serum, urine and pleural fluid salivary amylase levels parallel myeloma disease progression and response to treatment 4 , 5. Salivary amylase production in association with myeloma shows no immunoglobulin class specificity but levels relapse and remit with the disease 6…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that serum, urine and pleural fluid salivary amylase levels parallel myeloma disease progression and response to treatment 4 , 5. Salivary amylase production in association with myeloma shows no immunoglobulin class specificity but levels relapse and remit with the disease 6…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of the myeloma cell lines associated with hyperamylasaemia was a translocation of chromosome 1, which harbours the gene for amylase. [7][8][9] Shigemura et al 10 reported that in multiple myeloma with hyperamylasaemia, a majority of cases were due to salivary-type hyperamylasaemia (sialyl salivary-type amylase). In patients with amylase-producing multiple myeloma, the onset of hyperamylasaemia was associated with a rapid disease progression associated with extensive bone destruction and increased mortality.…”
mentioning
confidence: 99%